Evaluación del comportamiento agronómico de líneas promisorias de trigo (Tritucum aestivum L.) del INIAP bajo las condiciones agroecológicas de la Universidad Técnica de Cotopaxi Campus Salache, provincia de Cotopaxi 2021-2022. - Pichucho Otacoma, Cristian Manuel (2022)
Ecuador produces 2% of the wheat Ecuadorians consume, while 98% is imported; one of the problems is low productivity. This research was carried out at the Technical University of Cotopaxi - CEASA Campus in conjunction with the INIAP cereal program; the objective was to determine the agronomic behavior, severity of diseases, and yield in 4 promising lines and one improved variety of INIAP, under the environmental conditions to identify the lines or improved variety that demonstrates a good adaptation and performance for productivity in the area. A completely randomized block design (DBCA) was implemented in a total area of 72 m2, in which three replications were established, each with five treatments in plots of 3.6 m2, resulting in a total of 15 experimental units. For the evaluation of the promising lines and improved variety, the methodology proposed by the INIAP (2019) called Manual No. 111. "Parameters of evaluation and selection in cereals" was applied, which allowed the evaluation of indicators such as percentage of germination, the habit of growth, days to heading, plant height, straw type, spike size, number of grains per spike, reaction to diseases, the weight of grains per spike, yield, hectoliter weight, grain type, and color. In the data analysis, the normality test (Shapiro-Wilks) was carried out, and the data was submitted to a Tukey variance analysis at 5%; in the case of the variables that are evaluated employing scales, a table of averages was generated. The results determined for the adaptability parameter were TA-18-008 with 95%, plant vigor 1 on a scale of 3, growth habit 2 on a scale of 3, days to spike 56 days, type of straw 1 on the scale of 3, final height of 105.44 cm and spike size of 10.73 cm. For the severity parameter, for yellow rust (Puccinia striiformis) was TA-19-003 with 5% MR; for rust (Puccinia triticina) were TA-19-003, TA-19-008, and TA-20 -001; there was no presence of them; for BYDV (Barley Yellow Dwarf Virus) was TA-20-001 with a scale of 3 which did not show signs of dwarfism or reduction of tillering. For fusarium (Fusarium spp) were TA-20-001 and INIAP Imbabura 2014 with 14% damage to the spike; for coal (Ustilago tritici) was TA-20-001 with 5% damage to the spike. For the yield parameter, TA-18-008 with a weight of 6281.62 Kg/ha, followed by the improved variety INIAP IMBABURA 2014 with 6044.42 Kg/ha., while for hectoliter weight (kg hl-1) was INIAP IMBABURA 2014 with 74.42 (kg hl-1), followed by the promising line TA-18-008 with a weight of 67.69 (kg hl-1). -1). It is recommended to continue evaluating these improved lines and an improved variety of INIAP where favorable.